探析国际热爱大自然促进会作品《永伴幸福》的文化内——基于歌词与舞蹈动作的联动性分析 Exploring the Cultural Connotations of Eternal Happiness by The International Nature Loving Association: A Linkage Analysis of Lyrics and Dance Movements - Teti Ernita; Herman Herman (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2026)
摘要: 本文以国际热爱大自然促进会浪花青年团的作品《永伴幸福》为对象，通过歌词意象与舞蹈动作的联动性分析，探讨其文化内涵。研究表明，歌词以晨光、露水、彩虹、星辰等自然意象承载中华传统文化中仁爱、顺应自然及求真、向善、尚美的精神；舞蹈则通过舒展、托举、仰望、旋转等动作，将“天人合一”“和平与爱”“教育文化”“幸福文化”等理念转化为身体表达。歌词与舞蹈相互配合，构建了“意象—动作—情感”三位一体的文化传递机制。 关键词：国际热爱大自然促进会；大自然之舞；《永伴幸福》；文化价值；歌词与舞蹈的关联Abstract: This paper examines the cultural connotations of Eternal Happiness, a dance work by the Wave Youth Group of The International Nature Loving Association, through a linkage analysis of lyrical imagery and dance movements. The findings show that the lyrics use natural imagery—morning light, dew, rainbows, and stars—to convey core values of traditional Chinese culture, including benevolence, harmony with nature, and the pursuit of truth, goodness, and beauty. The dance translates abstract concepts such as "unity of heaven and humanity," "peace and love," "educational culture," and "culture of happiness" into physical expressions through movements like stretching, lifting, and gazing upward. Together, the lyrics and dance form a tripartite "image—movement—emotion" mechanism for integrated cultural transmission. Keywords: International Nature Loving Association; Nature Dance; Eternal Happiness; cultural values; connection between lyrics and dance